Structured intervention plan including component‐resolved diagnostics helps reducing the burden of food allergy among school‐aged children. Issue 1 (13th December 2018) - Savolainen, Johannes; Mascialino, Barbara; Pensamo, Elina; Åberg, K. Magnus; Silvan, Maija; Borres, Magnus P.; Korhonen, Krista
Abstract: Background: Food allergies can substantially burden patients and families by negatively affecting finances, social relationships, and personal perceptions of health. This study was performed under the Finnish Allergy Programme aimed at reducing avoidance diets to foods in schoolchildren by 50%. The main goal of this study was to investigate how many children could be freed from diet restrictions in a Finnish school district through a diagnostic algorithm including component‐resolved diagnostics and food challenge. The secondary aim was to provide a crude estimate of the burden of the elimination food diets in the region, and the savings associated with the proposed intervention. Methods: A total of 205 children on a food avoidance diet according to the school register because of food allergy were invited into the study. One hundred and fifty‐seven children were interviewed, tested for IgE to extracts and allergen components and food challenged in respective order. Results: After two years, 12 children still had an avoidance diet and three of them were treated successfully with sOTI; the rest suspended their avoidance diet (n = 134) or dropped out of the study (n = 11). The cost of the elimination diets was estimated in 172 700€ per year at start and 13 200€ per year at the end of the study; total savings were 128 400€ yearly. Conclusions: The results demonstrate a 65% reduction of avoidance diets to foods in school‐aged children, exceeding the 50% aim of the Finnish Allergy Programme. Therefore, it is possible to actively reduce the number of food allergy diagnoses that remain unmonitored in the society through a tailored diagnostic work‐up. Abstract :